The Formation of Abbreviated Loanwords in Japanese: A study of Ryakugo and Toujigo in Asahi Shimbun digital website of automotive-technology column - Sari, Witria Diah; Rasiban, Linna Meilia; Sutjiati, Neneng (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
In Japan, loanwords widely used in newspapers that make it difficult for readers to understand the information. As there is a need for a practical language, it has been proven by the more dominant use of abbreviations. In newspapers, abbreviations in loanwords are most commonly found in the field of automotive technology, but the use of abbreviations in newspaper must be taken into consideration, as it may be difficult to deliver the information. This study was arranged with the aim to find out, describe and analyse the formation of loanwords in ryakugoand toujigoform in the Asahi Shimbun Digitalwebsite. It is intended for Japanese learners to have a basic knowledge of the formation structure of the Japanese loanwords and to know the abbreviations and meanings of the automotive and technology fields term. The method used in this study is a descriptive qualitative analysis. The results of this study were obtained 79 data of ryakugoand toujigo, which in the formation of ryakugo were jouryaku, geryaku, and jougeryaku. While the formation of toujigo were keeping the first letter written with alphabet, keeping the first letter written with alpha-numeric, keeping the front–middle- in the first word and keeping two letters in the first word.